【Student Activity】[Conversation Circle-Opening] Culture Sharing & Language Exchange - 國際事務處; Office of International Affairs (國立陽明交通大學, 2024)
Welcome to our first Conversation Circle of the fall semester! We’re pleased to have you all with us today, and we hope you enjoyed the session and connected with fellow students!